PHANGS–JWST First Results: The 21 μm Compact Source Population - Hamid Hassani; Erik Rosolowsky; Adam K. Leroy; Médéric Boquien; Janice C. Lee; Ashley T. Barnes; Francesco Belfiore; F. Bigiel; Yixian Cao; Mélanie Chevance; Daniel A. Dale; Oleg V. Egorov; et al. (The Astrophysical Journal Letters, 2023)
We use PHANGS–James Webb Space Telescope (JWST) data to identify and classify 1271 compact 21 μ m sources in four nearby galaxies using MIRI F2100W data. We identify sources using a dendrogram-based algorithm, and we measure the background-subtracted flux densities for JWST bands from 2 to 21 μ m. Using the spectral energy distribution (SED) in JWST and HST bands plus ALMA and MUSE/VLT observations, we classify the sources by eye. Then we use this classification to define regions in color–color space and so establish a quantitative framework for classifying sources. We identify 1085 sources as belonging to the ISM of the target galaxies with the remainder being dusty stars or background galaxies. These 21 μ m sources are strongly spatially associated with H ii regions (>92% of sources), while 74% of the sources are coincident with a stellar association defined in the HST data. Using SED fitting, we find that the stellar masses of the 21 μ m sources span a range of 10 ^2 –10 ^4 M _⊙ with mass-weighted ages down to 2 Myr. There is a tight correlation between attenuation-corrected H α and 21 μ m luminosity for L _ν _,F2100W > 10 ^19 W Hz ^−1 . Young embedded source candidates selected at 21 μ m are found below this threshold and have M _⋆ < 10 ^3 M _⊙ .